Urban forests and their contribution to sustainable urban development in a global context: a case study of Multan, Pakistan - Aleha, Anum; Zahra, Syeda Mahwish; Qureshi, Sabeen; Shah, Shehroze; Marri, Sohrab Ahmed; Khan, Maska (Frontiers in Climate, 2024)
Currently, cities and towns are home to over half of the global population, and this percentage will rise over the coming decades. Cities can be wonderful homes to live in if planned and maintained properly, but most urban developments have noticeably caused environmental destruction, which in turn results in issues like urban heat islands, flooding, and air pollution. Cities require forests as their breathing organs. The study refers to the case of Multan City, where the climate is deteriorating at an alarming rate due to rapid urbanization and the lack of vegetation. The study aims to provide an urban green infrastructure (UGI), which abides by the key proactive resilience principles of effectiveness, diversity, dependence, durability, versatility, autonomy, planning, and adaptability. A strategic literature review has been done to study the effects of urban forests, and various studies were reviewed as per the methodology adopted worldwide. The policy frameworks of the Sustainable Development Goals (SDGs) and the New Urban Agenda (NUA) were considered while selecting sites for implementing urban forests. A five-point Likert scale questionnaire was developed for the participation of the community nearby. Ten different sites were selected in the city based on ownership and feasibility, irrespective of SDG, NUA, and community opinions. The study concludes with the design suggestion of one site as a prototype in the given context.